Magnesium-Molybate Compounds as Matrix for 99Mo/99mTc Generators - Fabiola Monroy-Guzman; Thania Susana Jimenez Martinez; Luis Carlos Longoria Gandara; Humberto Arriola (MDPI AG, 2011)
This work reports the preparation of a 99mTc generator based on conversion of 99Mo produced by neutron irradiation, into insoluble magnesium 99Mo-molybdates compounds as matrix. The effect of magnesium salt types and concentration, Mg:Mo molar ratios, pH of molybdate solutions, eluate volume as well as the addition order of molybdate and magnesium solutions' influences on the final 99mTc were evaluated. Polymetalates and polymolybdates salts either crystallized or amorphous were obtained depending on the magnesium salt and Mg:Mo molar ratio used in matrix preparation. 99Mo/99mTc generator production based on magnesium-99Mo molybdate compounds allow reduction of preparation time and eliminates the use of specialized installations. The best generator performances were attained using matrices prepared from 0.1 mol/L MgCl2·6H2O solutions, ammonium molybdate solutions at pH 7 and at a Mg:Mo molar ratio of 1:1.